Neoadjuvant systemic oncolytic vesicular stomatitis virus is safe and may enhance long-term survivorship in dogs with naturally occurring osteosarcoma - Kelly M. Makielski; Aaron L. Sarver; Michael S. Henson; Kathleen M. Stuebner; Antonella Borgatti; Lukkana Suksanpaisan; Caitlin Preusser; Alexandru-Flaviu Tabaran; Ingrid Cornax; M. Gerard O’Sullivan; Andrea Chehadeh; Donna Groschen; et al. (Molecular Therapy: Oncolytics, 2023)
Osteosarcoma is a devastating bone cancer that disproportionally afflicts children, adolescents, and young adults. Standard therapy includes surgical tumor resection combined with multiagent chemotherapy, but many patients still suffer from metastatic disease progression. Neoadjuvant systemic oncolytic virus (OV) therapy has the potential to improve clinical outcomes by targeting primary and metastatic tumor sites and inducing durable antitumor immune responses. Here we describe the first evaluation of neoadjuvant systemic therapy with a clinical-stage recombinant oncolytic vesicular stomatitis virus (VSV), VSV-IFNβ-NIS, in naturally occurring cancer, specifically appendicular osteosarcoma in companion dogs. Canine osteosarcoma has a similar natural disease history as its human counterpart. VSV-IFNβ-NIS was administered prior to standard of care surgical resection, permitting microscopic and genomic analysis of tumors. Treatment was well-tolerated and a “tail” of long-term survivors (∼35%) was apparent in the VSV-treated group, a greater proportion than observed in two contemporary control cohorts. An increase in tumor inflammation was observed in VSV-treated tumors and RNA-seq analysis showed that all the long-term responders had increased expression of a T cell anchored immune gene cluster. We conclude that neoadjuvant VSV-IFNβ-NIS is safe and may increase long-term survivorship in dogs with naturally occurring osteosarcoma, particularly those that exhibit pre-existing antitumor immunity.